Phytophthora cinnamomi Involved in the Decline of Holm Oak (Quercus ilex) Stands in Southern Italy. Issue 3 (21st March 2018) - Frisullo, Salvatore; Lima, Giuseppe; Magnano di San Lio, Gaetano; Camele, Ippolito; Melissano, Luigi; Puglisi, Ivana; Pane, Antonella; Agosteo, Giovanni Enrico; Prudente, Leonardo; Cacciola, Santa Olga
Abstract: During a survey of forest stands of holm oak (Quercus ilex) in the Salento peninsula, Apulia region (southern Italy), the oomycete Phytophthora cinnamomi was found to be consistently associated with tree decline and mortality in 7 municipalities of the province of Lecce. The pathogen was recovered directly from roots using a selective medium and from rhizosphere soil samples with leaf baits and subsequent isolation on the same selective medium used for direct isolation from roots. It was identified on the basis of morphological characters and by sequencing of the internal transcribed spacer (ITS) regions of the rDNA after amplification with conventional PCR. All P. cinnamomi isolates were A2 mating type and proved to be highly aggressive on seedlings of evergreen Mediterranean oak species, including holm oak. cork oak (Q. suber) and kermes oak (Q. coccifera). P. cinnamomi is a well know pathogen of several forest trees worldwide and on the basis of its widespread and consistent occurrence in forest stands of the Lecce province it was assumed to be the primary causal agent of holm oak decline in this area. Options for the management of this phytosanitary environmental emergence are discussed.